PENGEMBANGAN MEDIA POP “ UP BOOK PADA MATERI BANGUN RUANG UNTUK SISWA KELAS IV SD NEGERI 121309 GURILLA PEMATANGSIANTAR - Sirait, Ayu Roselita; Tarigan, Daitin; Simanungkalit, Erlinda; Mailani, Elvi; Winara, Winara (Universitas Negeri Medan, 2023)
This research and development aim to know the appropriateness, practicality and effectiveness of Pop-up Book learning media in solid figure material for tenth grade students of SD Negeri 121309 Gurilla Pematangsiantar. The research methodology employed is R&D (Research and Development) utilized 4D model (Four D™s) consisting of some phase which are Define, Design, Develop and Disseminate phase. Subject of the study is the fourth grade students of SD Negeri 121309 Gurilla Pematangsiantar for about 18 students. Object of the study is the development of pop-up book in solid figure material. In order to know the appropriateness, practicality and effectiveness, the media is evaluated by media expert, material expert and practicality expert. The effectiveness is measured by the test conducted to the students. The findings of the study revealed that pop-up book learning media in solid figure material is very appropriate to be used in learning process. The validation result of material expert is categorized 92% ˜very appropriate™, the validation result of media expert is categorized 90,66%˜very appropriate™ and the validation result of practicality expert is categorized 93, 33% ˜very appropriate™, and in effectiveness test by giving some questions for the students, gained the average score 83,05 points. Thus, this study concluded that pop-up book learning media in solid figure material for fourth grade students of SD Negeri 121309 Gurilla Pematangsiantar is very appropriate, practical and effective to be used in the learning process at school.